Potensi Pemanfaatan Sel Surya untuk Mendukung Energi di Bidang Pertanian - Tsamratul Fuadiyah; Sudarti Sudarti (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
Indonesia is a tropical country that has quite a lot of sunlight, so that it is very close to sunlight that cannot be used properly. Sunlight can be used as solar panels. Solar panels are a tool that is able to convert sunlight into electrical energy, solar panels themselves can take advantage of various fields of agriculture, one of which is agriculture. The use of energy derived from solar panels can increase agricultural yields. In tropical areas such as Indonesia, which has two rainy and dry seasons, it has abundant sunlight. This study aims to determine what potential can be produced by solar panels to support energy in agriculture. The research method used in this article is the journal review method by conducting literacy of national and international articles, with the number of journals reviewed as many as 25 journals, the journals analyzed and reviewed are journals that have the subject matter according to the research title, the results of the research will be explained in descriptive form and presented in tabular form. The results obtained after reviewing several articles that contain several uses of solar panels in agriculture that can be used for spraying, fertilizing, lighting, drying, irrigation, setting PH and temperature. The use of solar panels has many benefits for farmers because it has several advantages, namely it can save operational costs, is environmentally friendly, efficient, and can be used in the long term.